EffECT Of MULTI ENZYME SUPPLEMENTATION ON ILEAL DIGESTIBILITIES Of DRY MATTER, PROTEIN, ETHER EXTRACT, PHYTATE PHOSPHORUS AND NON-STARCH POLYSACCHARIDES IN BROILER DIET - A. Bharathidhasan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological trial was conducted to study the effect of multi enzyme supplementation on ileal digestibilities of dry matter (DM), crude protein (CP), ether extract (EE), phytate phosphorus (PP) and non-starch polysaccharides (NSPs) in terms of neutral detergent fibre (NDF), acid detergent fibre (ADF), hemicellulose and cellulose in broilers for a period of 0-6weeks. The broilers used in this trial were fed diets supplemented with enzyme at 0, 250, 500, 750 and 1000 g/ton of feed with a proportionate reduction in metabolizable energy (ME-1.25, 2.5, 3.75 and 5 %), crude protein (CP-0.75, 1.5, 2.25 and 3 %), methionine + cytine (0.5, 1, 1.5 and 2 %) and available phosphorus (2.2, 4.4, 6.6 and 8.8 %). The level of individual enzyme per gram of multi enzyme supplement was cellulase 146 IU, xylanase 241 IU, pectinase 98 IU, protease 74 IU, amylase 778 IU and phytase 33 IU. The ileal digestibility was conducted on 6 th week of trial. The ileal DM digestibility (%) was significantly (p<0.01) increased in 750 g and 1000 g enzyme supplemented groups than other treatment groups. The increase in ileal DM digestibility was significantly (p<0.01) higher (6.2 %) in the group fed with 750 g enzyme supplementation than control. The digestibility of ileal crude protein (%) significantly (p<0.01) increased in 500, 750 and 1000 g enzyme supplemented groups than control. The increase in ileal protein digestibility was 12.20 % in 500 g/ton, 9.90 % in 750 g/ton and 10.12 % in 1000 g enzyme supplemented groups than control. However a non significant difference was observed in ileal EE digestibility in all treatment groups. The ileal phytate phosphorus digestibility significantly (p<0.01) increased in all the enzyme supplemented groups (33.69 % in 250 g/ton, 38.75 % in 500 g/ton, 39.53% in 750 g/ton and 42.11% in1000 g/ton) than control (31.71%). A highly significant (P< 0.01) increase in ileal neutral detergent fibre (NDF) and hemicellulose was observed in 500 to 1000 g enzyme supplemented groups than control. Similarly significant (P<0.01) increase in ileal acid detergent fibre (ADF) and cellulose digestabilities (%) were observed in all enzyme supplemented groups than control. It was concluded that the multi enzyme supplementation at minimum inclusion level of 500 g per ton of feed increased the ileal digestibilities of CP, PP, NDF, ADF, hemicelluloses and cellulose by 12.20 %, 18.17 %, 13.57 %, 55.63 % 12.77 % and 52.64 % respectively than control in broiler diet than the control diet in broilers.